2005
DOI: 10.1186/1471-213x-5-20
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Bcl-xL in modulating apoptosis during development of Xenopus laevis

Abstract: Background: Apoptosis is a common and essential aspect of development. It is particularly prevalent in the central nervous system and during remodelling processes such as formation of the digits and in amphibian metamorphosis. Apoptosis, which is dependent upon a balance between pro-and anti-apoptotic factors, also enables the embryo to rid itself of cells damaged by gamma irradiation. In this study, the roles of the anti-apoptotic factor Bcl-x L in protecting cells from apoptosis were examined in Xenopus laev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Our previous study also showed that M50054 treatment from st. 27 to st. 34/35 did not induce eye defects (Kha et al, 2018). These data were also consistent with a previous study showing that overexpression of the anti-apoptotic gene, BcL-xL, during embryogenesis did not induce eye defects (Johnston et al, 2005). Thus, apoptosis does not appear to be required for eye development.…”
Section: Resultssupporting
confidence: 93%
“…Our previous study also showed that M50054 treatment from st. 27 to st. 34/35 did not induce eye defects (Kha et al, 2018). These data were also consistent with a previous study showing that overexpression of the anti-apoptotic gene, BcL-xL, during embryogenesis did not induce eye defects (Johnston et al, 2005). Thus, apoptosis does not appear to be required for eye development.…”
Section: Resultssupporting
confidence: 93%
“…S5D,E). In agreement with the notion that apoptosis was not involved in FGF-mediated specification of lateral GRP cells, injection of the anti-apoptotic B-cell CLL/lymphoma (bcl-XL) DNA construct, which inhibits chemically induced apoptosis (Johnston et al, 2005), into the lineage of the lateral GRP was unable to rescue SU5402-induced loss of nodal1/dand5positive GRP cells ( Fig. S5F-K).…”
Section: Fgf Signaling During Gastrulation Is Necessary For Lr Asymmetrysupporting
confidence: 83%
“…The apoptosis rescue experiment using Bcl-XL was performed by targeting 8 pg of Bcl-XL/CS2+ plasmid DNA (Johnston et al, 2005) into the left and right somitic GRP lineages (dorsolateral part of the 4-cell embryo). Embryos were treated with either DMSO or 60 µM SU5402 from stage 12-17, fixed and processed for in situ hybridization (ISH) using dand5-and nodal1-specific antisense probes.…”
Section: Analysis Of Apoptosis By Tunel Staining and Bcl-xl Injectionsmentioning
confidence: 99%
“…Proteins-Five members of the Xenopus Bcl-2 family of proteins (xBcl-w/xR1, xBcl-x L /xR11, xBax, xBid, and xBok) were functionally characterized in the previous studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In addition, partial or complete nucleotide sequences of 10 Bcl-2 family proteins (xBcl-2, xBcl-B, xBcl-G, xBcl2L12, xBcl2L13, xMcl-1, xBak, xBim, xBmf, and xNoxa) were deposited in the Xenopus nucleotide database, but the functions of their protein products remained uncharacterized (42)(43)(44).…”
Section: Identification and Rt-pcr Analysis Of Xenopus Bcl-2 Familymentioning
confidence: 99%
“…They are classified as either anti-apoptotic or pro-apoptotic, and the functional balance between these two groups controls the mitochondria-mediated intrinsic pathway of apoptosis. Although more than 10 members of the Bcl-2 family of proteins have been identified in Xenopus laevis (simply referred to as Xenopus hereafter), their functional characterizations are not yet complete (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%